Wet Chemical Synthesis of Nickel Nanostructures Using Different Capping Agents - Anuraj1, S.; Tejabhiram1, Y.; Mahdiyar1, B.; Shivaraman1, Ramaswamy; Gopalakrishnan1, C.; Karthigeyan2, A. (Asian Journal of Chemistry, 2013)
In this work, encapsulated nickel nanostructure were synthesized by wet chemical synthesis technique, using five different capping agents viz., cetyltrimethyl ammonium bromide (CTAB), starch, poly(ethylene glycol) (PEG), poly(vinyl pyrrolidone) (PVP), zeolite. Experiments were performed by varying the type and the concentration of the capping agents and the changes in morphology and crystallinity of the nickel nanostructures were observed. Morphology and crystallinity of the nanostructures obtained in these experiments were analyzed using field emission scanning electron microscopy (FESEM) and X-ray difractometry (XRD). The results incurred from these experiments suggest that the morphology and the crystallinity of the nickel nanoparticles can be controlled by using appropriate capping agent of appropriate concentration.